2005
DOI: 10.1002/hed.20228
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel node biopsy in squamous cell cancer of the oral cavity and oral pharynx: A diagnostic meta-analysis

Abstract: The sentinel node biopsy procedure has shown high sensitivity rates in pilot studies for oral and oropharyngeal squamous cell cancer across the globe and is reliable and reproducible. This study provides a firm evidence base for forthcoming trials on the role of sentinel node biopsy in head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(77 citation statements)
references
References 37 publications
3
72
0
2
Order By: Relevance
“…One hundred percent agreement was observed between SLN and END using the kappa statistic (k = 1). A meta-analysis of 19 studies showed 97.7 % sentinel node identification rate and 92.6 % sensitivity with a false negative rate of 3 % [9]. Mahima Rakheja et al, in his study, showed that sentinel lymph node biopsy is feasible and helpful in N0 necks for detecting in lymphatic spread of oral malignancy [10].…”
Section: Feasibility and Accuracymentioning
confidence: 99%
“…One hundred percent agreement was observed between SLN and END using the kappa statistic (k = 1). A meta-analysis of 19 studies showed 97.7 % sentinel node identification rate and 92.6 % sensitivity with a false negative rate of 3 % [9]. Mahima Rakheja et al, in his study, showed that sentinel lymph node biopsy is feasible and helpful in N0 necks for detecting in lymphatic spread of oral malignancy [10].…”
Section: Feasibility and Accuracymentioning
confidence: 99%
“…Thesent inel node (SN) procedure is applied in a variety of tumor types, including head and neck squamous cell carcinoma (HNSCC) (1,2). Although, in general, results in HNSCC are good, adequate detection of the SN in floor-ofmouth tumors, compared with other sites, appeared problematic, as illustrated by significantly lower sensitivity and negative predictive value (1).…”
mentioning
confidence: 99%
“…; ipsilateral). Here it is shown to be quite sensitive at 97% on average (range: 96-100%); however, there is still a small false negative rate (average 4%, range: 0-12%) [18][19][20]. Potential explanations for this are skip metastases and 'masking' of a sentinel node by adjacent radiotracer uptake from carcinomas of the floor of mouth particularly in level I.…”
Section: Sentinel Nodesmentioning
confidence: 80%